Comprehensive analysis of In0.53Ga0.47As SOI-FinFET for enhanced RF/wireless performance - Priyanka Agrwal; Ajay Kumar (Frontiers in Electronics)
This paper comprehensively analyses the RF (Radio Frequency) and wireless performance characteristics of high-k In0.53Ga0.47As silicon-on-insulator FinFET (InGaAs-SOI-FinFET). Firstly, the fundamental operating principles and unique features of InGaAs-SOI-FinFET are discussed, highlighting their three-dimensional fin structure and improved electrostatic control, which contributes to enhanced electrostatic integrity and reduced leakage currents compared to traditional CMOS technologies. The linearity performance of InGaAs-SOI-FinFET focuses on parameters such as third-order intercept point (IP3) and linearity metrics in analog circuits. The influence of device geometry, biasing schemes, and operating conditions on linearity characteristics and strategies for enhancing linearity while maintaining high-frequency performance is examined. Subsequently, an in-depth analysis of the RF performance metrics, such as fT, fMAX, TFP, GFP and GTFP. Thus, emerging trends and challenges in leveraging InGaAs-SOI-FinFET for RF and linearity-critical applications include circuit design, process integration, and reliability considerations.